"Ország az államban". Latgale történeti földrajza és nemzetiségi összetételének átalakulása a XX. században - Németh, Ádám (Közép-Európai Közlemények, 2012)
The first purpose of this publication is to present a short overview about the changes in the ethnic structure of Latgale after the first official Russian census (1897). The second goal is to analyze the regional distribution of these ethnic groups in Latvia and to diagnose the transformation of the ethnic diversity index in Latgale. Being on the frontier of German and Russian empires, and on the crossroad of trade routes, Latgale was always a point of intersection of Latvian, Lithuanian, Polish, Byelorussian, Russian and Jewish territories. Thus Latgale was one of the most ethnically diversed territory in Europein the end of the 19th century. Nowadays the diversity index is very high as well, although the ethnic composition of the region has changed dramatically since 1897. The publication would like to present: why and how?